2011
DOI: 10.1007/s10120-011-0080-y
|View full text |Cite
|
Sign up to set email alerts
|

Resection of liver metastases is beneficial in patients with gastric cancer: report on 15 cases and review of literature

Abstract: Background Although up to 9% of patients with gastric cancer develop liver metastases, liver resection is rarely performed because of co-existing non-curative factors. Furthermore, the benefit of liver resection is still controversially discussed. Our goal was to investigate the outcome of patients who underwent liver resection or radiofrequency ablation (RFA) for hepatic metastasized gastric cancer. Methods Retrospectively collected data from a prospectively maintained database were analyzed from 15 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…Fifty-three of these 76 articles were finally excluded from the meta-analysis because they did not report 5-year OS, they did not present OS for gastric cancer patients only, GC patients analyzed were less than 10, or publications were not available as full text. Therefore, 23 original reports (all retrospective cohort studies) had sufficient data to calculate the pooled 5-year OS after resection of liver metastases [4][5][6][7][8][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. There were no prospective studies, and most articles reported a single-or multi-center experience of patients and were published between 2001 and 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-three of these 76 articles were finally excluded from the meta-analysis because they did not report 5-year OS, they did not present OS for gastric cancer patients only, GC patients analyzed were less than 10, or publications were not available as full text. Therefore, 23 original reports (all retrospective cohort studies) had sufficient data to calculate the pooled 5-year OS after resection of liver metastases [4][5][6][7][8][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. There were no prospective studies, and most articles reported a single-or multi-center experience of patients and were published between 2001 and 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneous studies indicate a potential role of surgery in patients with metastatic gastric cancer (7,(12)(13)(14)(15)(16)(17)(18)(22)(23)(24)(25)(26)(27)(28). Similar as other aggressive treatment strategies, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been suggested as indicators for potential benefits from resection, i.e. response to induction therapy (12,13), number and pattern of metastasis (12)(13)(14)(15)(16)(17), performance status (14,15), and extent of the primary tumour (16,18). Previously published prognostic factors include the delivery of chemotherapy, resection, length of the primary tumour, number of metastatic sites and histopathological response (1,2,7).…”
Section: Introductionmentioning
confidence: 99%
“…However many patients were poor surgical candidates owing to insufficient cardiopulmonary function, old age, or other medical co-morbidities as well as those with pulmonary metastasis tumors, a life-threatening event with bad survival rates [3]. In recent years, tumor heating ablation such as radiofrequency ablation under the guidance of image has been proved to be an alternative treatment method for these patients with definite effects [4-8], and as a new minimally invasive technique, percutaneous microwave coagulation therapy (PMCT) has attracted a worldwide attention gradually in treating inoperable pulmonary malignancies.…”
Section: Introductionmentioning
confidence: 99%